Kajian Yuridis Peranan Alat Bukti TerhadapPutusan Bebas dalam Tindak Pidana Pemalsuan (Studi Kasus Terhadap Putusan Pengadilan Negeri Yogyakarta No. : 22 Pid.B 2016 PN.YYK - Suparno Suparno; Yanto Yanto; JS. Murdomo (Kajian Hasil Penelitian Hukum, 2019)
This thesis study aims, to know and examine the role and strength of evidence against free decisions in criminal cases of letter forgery, and to find out what things make legal judgments for judges in making free decisions. This research is a descriptive normative legal research using secondary data types. In this study, the data collection technique used was library research. Then the data obtained isthen studied, classified, and further analyzed according to the objectives and problems and to further strengthen the data in this study, the authors also conducted field research with interview methods with Resource Persons. Based on this research the results obtained to determine the role and strength of evidence. facts at the trial, as well as judges considerations in making free decisions against the accused. Besides that, the minimum requirements for two proofs and judges convictions were also fulfilled, so that the defendant could give a free verdict. That the evidence and evidence is very important from the criminal justice process. The evidence has an important role, both starting from the investigation, investigations in the police, until the Public Prosecutor is forwarded as a basis for making charges and demands. And then the evidence becomes the basis of the Judge judgment in displaying criminal case decisions, but the evidence is not enough if the convictions of the law enforcer will process the crime to continue, as if it were an important factor, both from the beginning by the investigator, by the Prosecutor The Public Prosecutor especially by the Panel of Judges to decide the case. If the evidence is not sufficient and or the judge beliefs do not exist, then the crime cannot be forced to proceed to the trial process. Therefore, in this case the author took a case study of decision No. 225  Pid.B  2016 PN YYK, in a case of fraud. And in the research of this case verdict, the panel of judges in its decision acquitted the defendant, because it was not proven and convinced the panel of judges.